Analyzing Lexical Density and Readability in IELTS Band 4 Students’ Writing Test - Putri, Aqia Syahnayya; Anshary, Elvira Putri; Sinar, T. Silvana; Maharani, Puan (International Journal Linguistics of Sumatra and Malay, 2024)
This study explores the lexical density and readability levels of writing produced by IELTS Band 4 students. The main objectives are to assess the lexical density and readability of their writing across ten writing tests. The study employs a descriptive qualitative research method, using data collected from 10 writing tests conducted by IELTS Band 4 students. Lexical density is determined using the "Analyze My Writing" website, while readability is assessed using the Flesch Reading Ease formula and scale. The findings reveal a wide range of lexical density, ranging from 46.98% to 63.93%, indicating varying levels of content richness and complexity in the students' writing. Similarly, readability scores vary significantly, with scores ranging from 34.21 to 66.32, reflecting differences in text difficulty and ease of comprehension. These findings underscore the diverse linguistic proficiency and accessibility of writing among IELTS Band 4 students.